Advanced Methods in Computer Graphics With examples in OpenGL - Mukundan, Ramakrishnan; SpringerLink (Online service) (London : Springer London : Imprint: Springer, 2012)
Advanced Methods in Computer Graphics provides an in-depth analysis  of a selection of topics that are important in the areas of character animation and game development.  The discussion of a wide range of algorithms and their implementation aspects presented in the book will serve as a useful reference for researchers and practitioners in computer graphics.  Students will find the book to be a valuable resource in their study of advanced graphics concepts.  The key topics covered in the book are  hierarchical modelling and transformations using scene graphs, skeletal animation, forward and inverse kinematics solutions,  quaternion based rotation interpolation, mesh processing and collision detection algorithms. The book also gives a thorough overview of splines, interpolation curves, and surface design methods. Features: Comprehensive coverage of a large collection of methods used in animation and game programming. Detailed description of the theoretical aspects of algorithms, complemented by examples, figures and pseudo-codes. Each chapter accompanied by a set of demonstration programs that clearly show the implementation and working of key algorithms. The C++ source code of all the examples, demos and classes for each chapter can be downloaded from the publisher's website, http://extras.springer.com/978-1-4471-2339-2. Ramakrishnan Mukundan is an associate professor in the Department of Computer Science and Software Engineering at the University of Canterbury, Christchurch, New Zealand. He has been teaching computer graphics courses at both undergraduate and graduate levels for the past twelve years.  .
Introduction -- Mathematical Preliminaries -- Scene Graphs -- Skeletal Animation -- Quaternions -- Kinematics -- Curves and Surfaces -- Mesh Processing -- Collision Detection -- Appendix A: Geometry Classes -- Appendix B: Scene Graph Classes -- Appendix C: Vertex Skinning Classes -- Appendix D: Quaternion Classes -- Index.
Keywords: Computer graphics; Computer Graphics